EFEKTIFITAS DAN DAMPAK PROGRAM KREDIT USAHA RAKYAT (KUR) TERHADAP PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Damayanti, Ni Nengah Sri; Budhi, Made Kembar Sri (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 9 (2023): Vol.12.No.9.SEPTEMBER. 2023[586-649], 2023)
KUR is in the form of a plan drawn up by the government, but the budget is sourced through the bank in full. The government distributes guarantees for KUR risks in the amount of 70% and the difference in the amount of 30% is distributed to the administering bank. KUR in the form of a government effort to support banks in channeling capital loans to cooperatives and SMEs. The target of this study is to analyze the effectiveness of the People's Business Credit program observed through income, stages and outputs in Micro, Small and Medium Enterprises of the Province of Bali and analyze the initial and after effects of this. This study was carried out using primary data using a quantitative method in the form of a questionnaire. The questionnaire method is used to analyze the effectiveness of the influence of the KUR program on MSME income. Through the results of the study, it can be seen if the three variables selected can be said to be classified as effective. Through the results of the paired t test, it can be concluded that the income of Micro, Small and Medium Enterprises after obtaining KUR is very dominant compared to the initial acquisition of KUR. keyword : People's Business Credit, Micro, Small and Medium Enterprises and Income